The Effect of Attendance and Work Motivation on Employee Performance at UPTD Puskesmas Sumbersari - Devi Mandaqini; Harmawan Teguh Saputra; Hanif Hadinata Utama (Universitas Ibn Khaldun Bogor, 2026)
This research tries to reveal the effects of attendance and motivation on staff performance at the Sumbersari Community Health Center (Puskesmas Sumbersari). Staff performance is an important factor in determining the quality of primary health care services provided to the community. Good staff performance is essential for patient satisfaction and the efficiency of health care delivery. Using a multivariate analysis approach, this study examined data from a total of 45 staff. A questionnaire was used to collect data, which was then analyzed using multiple regression analysis methods including R², t-test, and F-test. The results showed that staff performance was affected by attendance and motivation when considered together. Individually, motivation has a positive effect on employee performance, while attendance has no significant effect when examined together with job satisfaction. These results indicate that job satisfaction is the most important factor affecting employee performance. This highlights the need for organizational policies that promote motivation and create a supportive work environment. Therefore, when managing attendance discipline and focusing on improving employee performance and quality of care, management should prioritize strategies to improve employee motivation.